2001
DOI: 10.1542/peds.108.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Domestic Violence Screening in the Pediatric Setting

Abstract: Practitioners grossly underestimate the incidence of DV in their practices. Lack of education including knowledge of screening recommendations is a barrier to DV screening by pediatricians. Greater efforts are needed to educate pediatricians on DV for the AAP recommendations to be accepted.domestic violence, child abuse, screening, physician attitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
97
0
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 27 publications
5
97
0
6
Order By: Relevance
“…Although several obstacles exist for intimate partner violence screening in the ED, including fear of offending the patient, patient nondisclosure, 14 lack of resources, 15 lack of education of medical personnel, lack of specific treatment protocols, time constraints, and lack of support staff (eg, social workers), 16 our research demonstrates that universal intimate partner violence screening in the ED is possible and resulted in utilization of resources and safety measures. Moreover, in this large cohort of screened patients there was no evidence of any harm related to intimate partner violence screening and referral.…”
Section: Discussionmentioning
confidence: 80%
“…Although several obstacles exist for intimate partner violence screening in the ED, including fear of offending the patient, patient nondisclosure, 14 lack of resources, 15 lack of education of medical personnel, lack of specific treatment protocols, time constraints, and lack of support staff (eg, social workers), 16 our research demonstrates that universal intimate partner violence screening in the ED is possible and resulted in utilization of resources and safety measures. Moreover, in this large cohort of screened patients there was no evidence of any harm related to intimate partner violence screening and referral.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, there is clearly resistance to screening for parental domestic violence among pediatricians. One recent survey of Midwestern practitioners found that only 8.5% routinely screened [33]; a nationwide survey found the overall self-reported prevalence at 5%, with little improvement among recent cohorts [34]. The cited reasons are similar to those for practitioners treating adults: feelings of inadequate education and too little time, and concern about offending patients [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…16,63,64 Health providers report, however, that they often are unfamiliar with resources and do not know what to do if a patient discloses IPV to them. 12,28,51,[65][66][67][68] Unfortunately, little guidance exists on how to build these connections with victim-advocacy services, how to strengthen local connections, and how to nurture a collaborative relationship.…”
Section: Health Information Technology and Ipv Screening And Counselingmentioning
confidence: 99%